2014
DOI: 10.21101/cejph.a3925
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Rhinitis in the Slovak Republic - a Long-Term Retrospective Study

Abstract: Food industry, textile industry and agriculture were the most risky occupational environments. Workers in these sectors require preventive intervention. In case of showing rhinitis symptoms it is necessary to confirm the occupational aetiology of the disease by the objective diagnostic methods. Since occupational rhinitis mostly precedes the occupational asthma, the elimination from the workplace is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Notwithstanding this limitation, 6 of the 43 studies lacking cross‐tabulation (plus all four studies lacking objective pulmonary function tests) provided partial associational data, in which either: 1) the proportion of (presumed) occupational rhinitis cases developing occupational asthma (or vice versa) is reported (albeit in the absence of background rates); or 2) the sequence of development of nasal and chest symptoms are tabulated. Individual study characteristics of excluded studies, including study designs, principal exposure(s), health endpoint(s), number of subjects, and measure(s) of effect appear in Supplemental Tables S1‐S4. Briefly summarizing relevant data from these excluded studies, among workers undergoing objective pulmonary function testing, more than half of those diagnosed with occupational asthma to diphenylmethane diisocyanate (MDI), lupin ( Lupinus angustifolius ) flour, or ammonium persulfate (eg, hairdressers) also gave histories consistent with occupational rhinitis .…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding this limitation, 6 of the 43 studies lacking cross‐tabulation (plus all four studies lacking objective pulmonary function tests) provided partial associational data, in which either: 1) the proportion of (presumed) occupational rhinitis cases developing occupational asthma (or vice versa) is reported (albeit in the absence of background rates); or 2) the sequence of development of nasal and chest symptoms are tabulated. Individual study characteristics of excluded studies, including study designs, principal exposure(s), health endpoint(s), number of subjects, and measure(s) of effect appear in Supplemental Tables S1‐S4. Briefly summarizing relevant data from these excluded studies, among workers undergoing objective pulmonary function testing, more than half of those diagnosed with occupational asthma to diphenylmethane diisocyanate (MDI), lupin ( Lupinus angustifolius ) flour, or ammonium persulfate (eg, hairdressers) also gave histories consistent with occupational rhinitis .…”
Section: Resultsmentioning
confidence: 99%
“…In two other studies carried out in France during the period 1977-1998 and 1999-2003, bakers, hairdressers and health workers were found to be among the main occupations concerned by the OAR with a prevalence between 2.7% and 22.3% and 4.7% and 26% respectively [21]. A recent Slovak study was carried out in 2014 and the catering sector was responsible for half of the cases of OAR [22].…”
Section: Resultsmentioning
confidence: 99%
“…This finding may suggest women with rhinitis are less likely to seek employment in agriculture, or that women with rhinitis leave agricultural work. A study of occupational rhinitis in Slovakia also found a low prevalence of rhinitis in agricultural workers 40…”
Section: Discussionmentioning
confidence: 97%
“…A study of occupational rhinitis in Slovakia also found a low prevalence of rhinitis in agricultural workers. 40 Allergic skin conditions were more often associated with indirect measures of pesticide exposure such as agricultural work or government spraying of pesticides. Our findings were similar to research done in the United Arab Emirates (UAE) which found associations between agricultural pesticide exposures and skin conditions like eczema and itchy rash.…”
Section: Discussionmentioning
confidence: 99%